Effect of electrical properties of glass electrodes on the performance of RPC detectors for the INO-ICAL experiment. (31st August 2016) - Raveendrababu, K.; Behera, P.K.; Satyanarayana, B.
Abstract: The India-based Neutrino Observatory (INO) collaboration has chosen glass Resistive Plate Chambers (RPCs) as the active detector elements for the Iron Calorimeter (ICAL) experiment. In the present work, we study the electrical properties such as bulk resistivity and relative permittivity of the glasses from two different manufacturers and compared the performances of RPCs built using these glasses. We conclude that the glass electrodes with larger bulk resistivity and permittivity are better suited for manufacturing RPCs for the ICAL experiment, as these detectors could be operated at lower bias currents and voltages, and produce better time resolution compared to those built with glass electrodes of smaller bulk resistivity and permittivity.